STUDI PEMBERDAYAAN ANAK NELAYAN MELALUI PENDIDIKAN DI DESA PAKABBA KECAMATAN GALESONG UTARA KABUPATEN TAKALAR - Erman Syarif; Syamsunardi Syamsunardi (UNIVERSITAS NEGERI MAKASSAR, 2021)
ABSTRACTThis study aims: 1) To find out the parents' perspective on children's formal education and 2) To find out what factors influence the sustainability of children's education. This type of research is qualitative research. The research location is in Pakkaba Village, North Galesong District, Takalar Regency. There are three stages in this research, namely data collection, analysis and presentation of the results of data analysis/checking the validity of the data. Collecting data through observation, interviews, and documentation. Data verification strategy with data reduction, data categorization, data display, and conclusion (verification). The results of the study show that 1) the level of public knowledge of children's education is very diverse, but basically they are already aware of the importance of education for their children for the future, 2) the factors that influence the education of fishermen's children are 4 factors, namely: economic factors, environmental factors, parental education factors and motivational factors. It is hoped that parents and the community will always provide guidance and supervision of children's education, for the realization of better education and children's personality.